DETERMINATION OF ADEQUACY BREAST MILK PRODUCTION - Ridha Wahyuni; Erika Lestari; Khoirul Anam (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Underfive mortality in the first month of life is still high, with breastfeeding (ASI) will reduce 22% of infant deaths under the age of 28 days, so it is necessary to do an assessment of the adequacy of breast milk production in postpartum mothers. The purpose of this study was to determine the determination of the adequacy of breast milk production in postpartum mothers. This research is a descriptive study with the number of respondents 25 postpartum mothers day 3 to 7. Based on the results of research from 25 respondents, 100% of respondents were productive (20-35 years), 96 respondents worked in Household Care, 100% of respondents applied positions correct breastfeeding and 73% of respondents have adequate milk production. The conclusion of this study is that there are 73% of respondents having adequate breastfeeding with sufficient determination of the productive age, MRT work and applying the correct breastfeeding position.